ANALISIS PENGARUH KEBIJAKAN PENGUMUMAN DEVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK JAKARTA PERIODE 2002-2004 - Susanto, Barkah (Jurnal Analisis Bisnis Ekonomi, 2006)
Every company in its capital allocation is always given on two interconnected and important problem, that is decisionof long-range expenditure and invesment. Despitefully still there are one problem again that is containing dividend decision about how many dividend which must be alloted o stockholder. Policy of dividend Announcement present one of important decision in its bearing with the effort to maximize the company value influenced by invesment decision, capital structure (decision of accomplishment of fund requirement) and policy of itself dividend. Persuant to the kondidi hence this research take the title : "Influence of Policy of Dividend Announcement to Share Price at Company of Food and Beverage In Jakarta Stock Exchange" This period research at period 2002-2004. Intention of this research is to know whether/what there influence of policy of dividend announcement to share price at company of food and beverage Jakarta Stock Exchange. Company which selected as sample in this research is company of food and beverage enlisted in Jakarta Stock Exchange (BEJ). Data taken away from by corner of stock pf University of Muhammadiyah Magelang. Election sample done by purposive is random sampling belongs 12 company which at one blow made by sample in this research. Method used in this analysis is examination by Paired Samples T Test. Result of enumeration analyse above knowable that biggest mean from abnormal return that happened three day after announcement deviden, that is equal tp 0,008228. While mean lowered abnormal level return is 2 (two) day after announcement deviden, that is equal to -0,003658. Result analyse by using Paired Sample T-Test obtained by value of equal to 3.938, hence the value fulfill the criterion in hypothesis acceptance.